Estudio fitoquímico preliminar de plantas de la familia Compositae de Costa Rica. I. Lactonas sesquiterpénicas - Cicció, José F.; Calzada, José G.; Montero, Walter; Poveda, Luis J. (Revista de Biología Tropical, 1978)
In a preliminary study of thirty species of the family Compositae from Costa Rica, the presence of sesquiterpene lactanes was established through the infrared spectra of the purified extracts. The structures of four isolated lactones are under investigation.